Perencanaan dan Pengendalian Produksi Dalam Sistem Logistik (Pendekatan Berbasis Praktikum Laboratorium) - Ruswandi, Nanda; Herlina, Rohma; Suri, Faras Karningtia; Dianisa, Pramesti Adwinda; Sandi, Evelyn; Sukarno, Iwan; Liperda, Rahmad Inca; Lusiani, Mirna (UNISTEK, 2021)
The concept of Production Planning and Control is closely related to logistics activities, including in determining the production of a product. Production planning and control aims to get a complete picture of how to plan and control production in the industry of each company, so that all costs can be reduced. Production planning, Rough Cut Capacity Planning (RCCP), Material Requirement Planning (MRP), Capacity Requirement Planning (CRP), and Line Balancing are some of the steps that need to be done in providing an overview of the production planning and control system at the "Tamiya" Company. Production planning results in the amount of "Tamiya" production in a certain period by considering SEE and the most appropriate production strategy that results in total costs. MPS validation considerations are the output of the RCCP calculation, a comparison of the ratio of the required capacity to the capacity of the company. The MRP stage reduces production due to material unavailability, the result is the best material scheduling based on the lot sizing method which provides the lowest cost. CRP generates Planned Input and Planned Output per work station to see the balance between load and capacity. Line Balancing functions to balance assignments through the Ranking Position Weight (RPW) and Presedence Diagram methods, getting results in the form of updating the layout of the assignment so that the efficiency of the production line can be improved